COMPLIANCE AND ADHERENCE OF PATIENTS WITH DIABETIC MACULAR EDEMA TO INTRAVITREAL ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY IN DAILY PRACTICE. Issue 12 (December 2018) - Weiss, Maximilian; Sim, Dawn A.; Herold, Tina; Schumann, Ricarda G.; Liegl, Raffael; Kern, Christoph; Kreutzer, Thomas; Schiefelbein, Johannes; Rottmann, Miriam; Priglinger, Siegfried; KortUEm, Karsten Ulrich
Abstract : Purpose: We assessed differences in compliance and adherence (lateness of patients, visual acuity, reasons for abstaining) between patients with diabetic macular edema (DME) and patients with age-related macular degeneration (AMD), both under anti–vascular endothelial growth factor therapy. Methods: We included 136 patients with DME (36% women, 65 years, 22 visits, 13.9 injections, and 29.9 months of follow-up) and 109 patients with AMD (59% women, 76 years, 20 visits, 14.7 injections, and 22.3 months of follow-up) (minimum follow-up of 12 months and at least 5 injections). We assessed missed appointments (lateness >14 days) and therapy break-offs (lateness >100 days). All delayed patients were called and interviewed for abstaining reasons. Results: Forty-six percent of patients with DME and 22% of patients with AMD had at least one break-off. Thirty-five percent of patients with DME and 50% of patients with AMD were always on schedule. In patients with DME, there was significant correlation ( P = 0.017) between the number of break-offs and change of visual acuity. In 60% DME and 38% AMD of break-off cases, visual acuity was worse than the before break-off. The most common reason for abstaining was comorbidities (33% AMD and 20% DME). Conclusion: There are significant differences between patients with AMD and DME regarding compliance and adherence, which also affects outcome. Strategies to tie patients with DME to costly intravitreal therapy need to be developed to improve outcomes and efficacy. Abstract : Compliance and therapy adherence are important for good visual acuity outcomes after anti–vascular endothelial growth factor therapy in patients with diabetic macular edema. In this study, the authors found significant differences in behavior compared with age-related macular degeneration patients under anti–vascular endothelial growth factor therapy. Furthermore, significant correlations between numbers of therapy break-offs and visual acuity exist.